Is ChatGPT ready to change mental healthcare? Challenges and considerations: a reality-check - Pandya, Apurvakumar; Lodha, Pragya; Ganatra, Amit (Frontiers in Human Dynamics, 2024)
As mental healthcare is highly stigmatized, digital platforms and services are becoming popular. A wide variety of exciting and futuristic applications of AI platforms are available now. One such application getting tremendous attention from users and researchers alike is Chat Generative Pre-trained Transformer (ChatGPT). ChatGPT is a powerful chatbot launched by open artificial intelligence (Open AI). ChatGPT interacts with clients conversationally, answering follow-up questions, admitting mistakes, challenging incorrect premises, and rejecting inappropriate requests. With its multifarious applications, the ethical and privacy considerations surrounding the use of these technologies in sensitive areas such as mental health should be carefully addressed to ensure user safety and wellbeing. The authors comment on the ethical challenges with ChatGPT in mental healthcare that need attention at various levels, outlining six major concerns viz., (1) accurate identification and diagnosis of mental health conditions; (2) limited understanding and misinterpretation; (3) safety, and privacy of users; (4) bias and equity; (5) lack of monitoring and regulation; and (6) gaps in evidence, and lack of educational and training curricula.